Allah is the Creator: An Analysis of Hadiths on Human Creation and Destiny - Alfani, Mukhammad; Istifarin, Nur Annisa (Medina-te : Jurnal Studi Islam, 2023)
This article human creation and the concept of destiny according to Islamic teachings, using qualitative research methods. The process of human creation is explained in the Qur'an and hadith, including the stages of embryonic development in the womb according to the 4th Hadith of arbain. In addition, there is an explanation of the four levels of destiny that must be believed, as well as the redaction of the hadith that explains the process of human creation and the granting of destiny by Allah. Hadith Arbain 4 explains the process of human embryo development in the womb, starting from the stage of nutfah (sperm) to the blowing of the spirit. At the stage of spirit inhalation, Allah determines human destiny, including sustenance, death, charity, and happiness. Although destiny has been written, humans still have free will to do good or bad. The text emphasizes the importance of understanding the messages in this hadith and applying them in daily life. The implementation of this hadith can be done by developing gratitude, understanding destiny, respecting human position, and optimizing potential and responsibility. Thus, an understanding of human creation and destiny in Islam can serve as a foundation for individuals to live life with full awareness of the destiny that has been set, but still be responsible for their actions and choices fertilization.